The effect on blink frequency of a selective blue-filtering photochromic lens in patients with benign essential blepharospasm - Monschein, Tobias; Zrzavy, Tobias; Weber, Corinna; Kuzmina, Zoya; Gutstein, Walter; Sycha, Thomas (Frontiers in Neurology, 2023)
Objective The aim of this clinical study was to assess the impact of a non-invasive selective blue-filtering photochromic lens coating Crizal Prevencia on the treatment and response of benign essential blepharospasm (BEB). Patients and methods Twenty-four patients were recruited in the outpatient clinic of the Medical University of Vienna in a randomized, double-blind, cross-over study design. Blink frequencies were assessed in patients with BEB before and 14 days after intervention with either a filtering ophthalmic lens or a placebo lens, respectively. Outcome parameters include sub-group analysis of a blink frequency under six different conditions: three photopic conditions, one resting condition, one reading condition, and one video game condition. Results From 24 recruited patients, 15 patients were available for final analysis. Comparing the optical blue filtering lens to placebo, showed a reduced blink frequency in specific subtests, but not compared to baseline. Discussion In conclusion, optical filtering glasses might have a beneficial effect on BEB and provide a non-invasive therapeutic add-on option, in addition to botulinum neurotoxin therapy, for patients with BEB and should necessarily be further investigated in a multicenter setting, resulting in larger sample sizes to gain valid information about the effect of photochromic blue filter glasses in BEB. Clinical trial registration: https://drks.de/search/en/trial/DRKS00032135, DRKS00032135.